Corpus-Based Study of Near-Synonym and Antonymy Fact in Turkish Language - Ayşe Eda Gündoğdu (Dilbilim Araştırmaları Dergisi)
The main purpose of this study is to reveal the near-synonym and antonymy relationality between the denotative and figurative semantic aspects of such adjectives as cold / cool / warm / hot and high / low / long / short which can be evaluated in the same sense in Turkish language. In this framework, it has been revealed under which conditions the inter-lexical semantic relation can be achieved and in what kind of contextual situations this relation may differ as the referential meaning of the abovementioned adjectives progresses from concrete to abstract (i.e. from denotative aspects into figurative semantic dimension). In this study, the method of descriptive scanning has been used, and the results of the study have been interpreted through the percentage and frequency tables. In conclusion, it has been observed that the near-synonym and antonymy aspects generally remain at the denotative level and the establishment of abovementioned sense relations becomes more difficult as the meaning gets more abstract.